Knowledge, attitudes and practices (KAP) on fecal sludge resource recovery and reuse in Dar es Salaam, Tanzania - Isabela T. Mkude (IWA Publishing, 2021)
Resource recovery and reuse (RRR) of fecal sludge (FS) from onsite sanitation systems describes the concept of turning human waste into valuable end products. However, studies on peoples' perceptions of FS-derived products are still limited. Guided by the knowledge, attitudes and practices framework, and data from a survey of 395 households, focus group discussions and key informant interviews, this article explores how residents in three unplanned settlements of Dar es Salaam, Tanzania view FS RRR (FS-RRR). Results indicate that residents' knowledge about FS-RRR is moderately low. Moreover, residents generally have negative attitudes toward using FS-derived products, except for those not directly consumed, such as biogas or FS-briquettes. Additionally, only a few residents have engaged in any FS-RRR practices. We conclude that to increase local acceptance of FS-RRR will require significant efforts by a multitude of actors, not least to dispel myths linked to human waste, but also to raise awareness and demonstrate the benefits and safety of FS-derived products. The Tanzanian government must take the lead in this process and should start by prioritizing the improvement of fecal sludge management (FSM) to enable such a shift. HIGHLIGHTS The existing knowledge, attitudes and practices on fecal sludge resource recovery and reuse among residents were explored in three selected unplanned settlements.; Low-to-moderate knowledge of resource recovery and negative attitudes have been identified.; Training, awareness campaigns, public participation and private sector involvement are recommended.;